(untitled) (International journal of artificial intelligence, 2025)
The professional development of English teachers is essential to ensuring high-quality language instruction in an increasingly globalized world. This article explores the fundamental requirements for English teachers, including language proficiency, pedagogical expertise, classroom management, technological integration, and intercultural competence. Emphasizing the importance of lifelong learning, it highlights strategies for continuous professional development through training, mentorship, and reflective practice. By meeting these requirements, educators can enhance their teaching effectiveness and create dynamic, culturally responsive learning environments.